The Role of Rho-associated Kinase in the Cognitive Benefits of the ACE Inhibitory Peptide LAP for Hypertension - Huang, Junling; Wang, Haifeng; Liu, Yang; Luo, Bangzhen; Fang, Hong; Luo, Ming (Current Molecular Medicine, 2025)
<span class=
Keywords: LAP (Leu-Arg-Pro-Val-Ala-Ala)